ASEAN Regional Guidelines for Promoting Climate Smart Agriculture (CSA) Practices Volume II - Association of Southeast Asian Nations (2017)
This Guideline is a result of ongoing or completed initiatives and knowledgesharing events promoting climate resilience by the ASEAN Climate Resilience Network (ASEAN-CRN) and its partners. ASEAN-CRN is under the purview of the ASEAN Technical Working Group of Agriculture and Research Development (ATWGARD), an organic unit under the ASEAN Ministers of Agriculture and Forestry (AMAF). The chapters represent topics of keen interest to the member states, which also coincided with practices being promoted by development partners and stakeholders in the region.